Asylums : essays on the social situation of mental patients and other inmates - Goffman, Erving (Penguin books, 1961)
First an exposition is given of characteristics which mental hospitals share with other "total institutions" (e.g., jails, military camps, monasteries) and how their inmates adjust in similar ways to them. This process is then described as the "moral career of the mental patient," and the situation is further elaborated by a field study on "the underlife of a public institution: study of ways of making out in a mental hospital." Finally "some notes on the vicissitudes of the tinkering trades" are made in regard to "the medical model and mental hospitalization."